Changes in the digestive gland of Euphausia superba during short-term starvation: lipid class, fatty acid and sterol content and composition - Virtue, P; Nicol, S; Nichols, P (Marine Biology, 1993)
During a period of short-term (19 d) starvation,total lipid in the digestive gland of Euphausia superbaDana decreased from 21 to 9% dry weight. Total lipid perdigestive gland decreased significantly during starvationcompared to Day 0 individuals, falling from 1960 (_+ 172)to 385 (_+81)gg. Polar lipid was the major lipid classutilised during starvation, falling from 1510 (,.-225) to177 (__ 46) gg per digestive gland (76 to 45 %). Absolutelevels of triacylglycerol fell from 300 (_+41) to 76(_+5) gg; however, relative levels remained unchanged.The relative level of free fatty acid increased significantlywith starvation (4 to 39 %) with absolute levels rangingfrom 79 (+ 1) to 156 (_+20) ~tg per digestive gland. Absolutelevels of all fatty acids per digestive gland declinedcontinually until the end of the starvation period. Thelong-chain polyunsaturated acids eicosapentaenoic(20:50)3) and docosahexaenoic (22:60)3), decreased withstarvation from 37 to 26% and 15 to 10%, respectivelywhereas the saturated fatty acid, palmitic acid (16:0),increased from 15 to 22%. Cholesterol, the major sterolin this organ, increased from 17 (+ 20) to 44 (___ ] 3) gg perdigestive gland by Day 3, and by Day 19 had returned tolevels found in the digestive gland of Day 0 individuals.Desmosterol followed a similar pattern to cholesterol,increasing from 3 (__ 1) l~g per digestive gland on Day 0to 11 (+_4) gg on Day3, and falling to 2 (+-l)Bg onDay 19. Other sterols in the digestive gland, predominantlyof algal origin, fell from the levels found in Day 0individuals to near zero amounts by Day 6. The digestivegland of E. superba plays a dynamic role during shorttermstarvation in terms of lipid content and composition.The relative levels of polar lipids, free fatty acidsand cholesterol in the digestive gland may provide reliableindices of the nutritional condition of E. superba inthe field. Sterols in the digestive gland are indicative ofrecent dietary composition of krill, and may also be usedto quantify dietary input from individual phytoplanktonicspecies.